The Socio- Economic Impact of Urban Redevelopment in Gondar City - Mohammed, Seid Jibril; Yehualashet, Yemataw Wendie; Dejenie, Muluken Fikadie (Innovare Journal of Social Sciences, 2016)
Abstract This study aims to identify the socioeconomic impact of urban redevelopment on the resellers''. It takes a form that emanates from not only after the displacement takes place but also the process of relocation. Identifying the change in income, means of livelihood, social bond were the specific objectives. A cross – sectional study design was employed and both forms of data collected through structured questionnaire, semi – structured interview and observation. It has indicated, the relocation scheme affect the relocated community negatively. These can be outlined as occupational, income, and social interaction. The change in occupation changed their income level. Their social interaction score has decreased as compared to their former residence. Both the intensity of neighborhood based interaction and the intensity of attachment to neighborhood are decreasing. This study gave remarkable concern on how the process of relocation undertaken. In contrast to the established rules of project execution, the study reveals the opposite. The necessary input for a project, i.e. participation, was almost abandoned and it only restricted in giving information. Therefore, we recommend towards the planning and execution process. Including improving the existing situation and preparing for the proper implementation of future projects. Key words: socio-economic impact, urban redevelopment